INCLUSION, CHILDHOOD AND TEACHING PRACTICE. ASSUMPTIONS AND TENSIONS IN THE CURRICULUMPROPOSED FOR THE INITIAL EDUCATION OF THE PROVINCE OF CHACO - Mariela del Carmen Fogar; Carlos Alberto Silva (Universidad Nacional del Nordeste, 2016)
Recentre search developments about theoretical inquiry into the Curriculum of Initial Education of the province of Chaco, through inclusive political categories, initial education and childhood. The theoretical approach is understood as a way of representing reality through concepts that operate as assumptions. The inquiry follows a qualitative logic with documentary analysis. He is part of the ongoing research project "public policies for children: incidence of the obligatory nature of the initial level in the construction of the subjectivity of children from the neighborhood Molina Punta from Resistencia, Chaco", undertaken by Seminary education and society. Curriculum change in NI, was part of inclusive education policies for children implemented by the national Government in the period 2003 / 2015. Education as a practice linked to material, social and symbolic conditions, historical, co-producer of subjectivities (Puiggros, 1995) and social (Frigerio, 2001) is assumed. Frigerio (2005) and McLaren (1998) understand this as a political practice, which includes a cultural and economic policy of distribution of knowledge, desires and identities. This article analyzes the curriculum in association with historical processes on which is inscribed and tensions in the dynamics between the proposed curriculum adjusted to an idea of inclusive education function, and its construction in practice.